2019
DOI: 10.1080/00313831.2019.1570547
|View full text |Cite
|
Sign up to set email alerts
|

“Can do!” Teacher Promotion of Optimism in Response to Student Failure Expectation Expressions in Classroom Discourse

Abstract: This study offers detailed observational analyses of how teachers use optimism as an instructional resource when responding to students' failure expectation displays in classroom situations. The results were based on video-recordings of 25 lessons in two Finnish part-time special education settings, analysed by means of applied conversation analysis. The results showed that the teachers boosted optimism by inverting students' negative utterances, giving examples of successful experiences of peers, offering pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The perspective of the two is the same, namely that it is important to apply positive psychology in schools to increase the level of well-being among students and teachers [38]. At the same time, the Merdeka Belajar program also emphasizes evaluating the school atmosphere, class, and how to create happier schools to support student achievement [39]. This program also emphasizes objective evaluation of student character, the welfare of school members included in the school curriculum, which is in fact in line with PISA's concern since 2000 until now.…”
Section: Resultsmentioning
confidence: 99%
“…The perspective of the two is the same, namely that it is important to apply positive psychology in schools to increase the level of well-being among students and teachers [38]. At the same time, the Merdeka Belajar program also emphasizes evaluating the school atmosphere, class, and how to create happier schools to support student achievement [39]. This program also emphasizes objective evaluation of student character, the welfare of school members included in the school curriculum, which is in fact in line with PISA's concern since 2000 until now.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that optimistic students are more academically engaged compared to non-optimistic students (Ouweneel et al. , 2011; Vehkakoski, 2020), are psychologically resilient (Kapikiran, 2012), have positive emotions (Bazargan-Hejazi et al. , 2021), lower psychological maladjustment and career planning (Vehkakoski, 2020), and a high-quality life (Tavakoly Sany et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…, 2011; Vehkakoski, 2020), are psychologically resilient (Kapikiran, 2012), have positive emotions (Bazargan-Hejazi et al. , 2021), lower psychological maladjustment and career planning (Vehkakoski, 2020), and a high-quality life (Tavakoly Sany et al. , 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimism boosting performance evaluation (Vehkakoski, 2020) Is there anything negative in your task performance? If yes, invert your comments by giving examples of your successful positive performances in the past.…”
Section: Positive Future Perspectivementioning
confidence: 99%